Atypical ductal hyperplasia is a multipotent precursor of breast carcinoma. Issue 3 (22nd April 2019) - Kader, Tanjina; Hill, Prue; Zethoven, Magnus; Goode, David L; Elder, Kenneth; Thio, Niko; Doyle, Maria; Semple, Timothy; Sufyan, Wajiha; Byrne, David J; Pang, Jia‐Min B; Murugasu, Anand; et al.
Abstract: The current model for breast cancer progression proposes independent 'low grade (LG)‐like' and 'high grade (HG)‐like' pathways but lacks a known precursor to HG cancer. We applied low‐coverage whole‐genome sequencing to atypical ductal hyperplasia (ADH) with and without carcinoma to shed light on breast cancer progression. Fourteen out of twenty isolated ADH cases harboured at least one copy number alteration (CNA), but had fewer aberrations than LG or HG ductal carcinoma in situ (DCIS). ADH carried more HG‐like CNA than LG DCIS (e.g. 8q gain). Correspondingly, 64% (7/11) of ADH cases with synchronous HG carcinoma were clonally related, similar to LG carcinoma (67%, 6/9). This study represents a significant shift in our understanding of breast cancer progression, with ADH as a common precursor lesion to the independent 'low grade‐like' and 'high grade‐like' pathways. These data suggest that ADH can be a precursor of HG breast cancer and that LG and HG carcinomas can evolve from a similar ancestor lesion. We propose that although LG DCIS may be committed to a LG molecular pathway, ADH may remain multipotent, progressing to either LG or HG carcinoma. This multipotent nature suggests that some ADH cases could be more clinically significant than LG DCIS, requiring biomarkers for personalising management. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.